Wavefront-sensorless adaptive optics with a laser-free spinning disk confocal microscope - Hussain, SA; Kubo, T; Hall, N; Gala, D; Hampson, K; Parton, R; Phillips, MA; Wincott, M; Fujita, K; Davis, I; Dobbie, I; Booth, MJ (Wiley, 2020)
Adaptive optics is being applied widely to a range of microscopies in order to improve imaging quality in the presence of specimen-induced aberrations. We present here the first implementation of wavefront-sensorless adaptive optics for a laser-free, aperture correlation, spinning disk microscope. This widefield method provides confocal-like optical sectioning through use of a patterned disk in the illumination and detection paths. Like other high-resolution microscopes, its operation is compromised by aberrations due to refractive index mismatch and variations within the specimen. Correction of such aberrations shows improved signal level, contrast and resolution.